MANAGEMENT OF COMMUNITY SERVICE OF ISLAMIC UNIVERSITIES AT BANTEN - Gunawan, Agus (International Journal of Research -GRANTHAALAYAH, 2017)
This study used a qualitative naturalistic approach. Purposive sampling technique used by researchers as an instrument. Techniques of collecting data through interview, observation and documentation. Steps to be taken in data processing is: (1) test the validity of data is carried out through the triangulation of data, member check, and audit trail; (2) The data analysis was done in a sustainable and developed throughout the program; (3) Data Reduction; (4) Data presentation; and (5) Make a conclusion. Forms of community service activities developed and conducted by the University of Muhammadiyah Tangerang include: Field Work Experience, Founding Village, Campus of Environment, Partnership Cooperation, Training and Publishing journals. While the form of community service activities developed and conducted by the University Mathla'ul Anwar Pandeglang includes: paper publication activities, upgrading activities, assistance to non-formal education, assistance to the efforts of eradicate illiteracy, sending teams sports and art, the delivery of missionary endeavor, community development, coaching the boarding school students, also assistance to businesses that do not make a profit